1998
DOI: 10.1097/00007632-199801010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Analysis of Lumbar Disc Changes Below Scoliosis Fusions

Abstract: If these results are corroborated in a larger sample size, surgeons who manage deformity may have to consider altering fusion levels at the time of fusion based on magnetic resonance imaging predictors. The present data may help to inform patients about the risk of developing junctional degenerative changes and potential symptoms from these changes below scoliosis fusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…2,18,57,58 We could not verify any dysfunction in any of our variables between those with a fusion ending below L3 versus those with a more proximal ending of the fusion. Helenius et al 10 reported in 2002 results of 80% of initial 98 patients undergoing Harrington Instrumentation for AIS 20.8 years (mean) after surgery with a curve deterioration of 7 degrees (mean).…”
Section: Discussionmentioning
confidence: 75%
“…2,18,57,58 We could not verify any dysfunction in any of our variables between those with a fusion ending below L3 versus those with a more proximal ending of the fusion. Helenius et al 10 reported in 2002 results of 80% of initial 98 patients undergoing Harrington Instrumentation for AIS 20.8 years (mean) after surgery with a curve deterioration of 7 degrees (mean).…”
Section: Discussionmentioning
confidence: 75%
“…This process is known for originating an increased load transfer on the disc above the fusion [1]. The disc below the fused level is also subjected to new strains [2] related to a translational (shear) motion [17] that may lead to pain. This could also apply to the sacroiliac joint.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1998, Balderston et al [19], unlike Harding et al [20], noted the degeneration of underlying discs and a correlation between this degeneration and the worsening of lumbar pain After 9.3 years of follow-up, the latter found that revision surgery was necessary in 11.7% especially in patients with postoperative imbalance. Edwards et al [21] found disc degeneration in 61% of 34 patients who underwent arthrodesis up to L5.…”
Section: Mechanical Complicationsmentioning
confidence: 99%